2020
DOI: 10.1111/ecog.05143
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of diversity estimators applied to a database of host–parasite associations

Abstract: Understanding the drivers of biodiversity is important for forecasting changes in the distribution of life on earth. However, most studies of biodiversity are limited by uneven sampling effort, with some regions or taxa better sampled than others. Numerous methods have been developed to account for differences in sampling effort, but most methods were developed for systematic surveys in which all study units are sampled using the same design and assemblages are sampled randomly. Databases compiled from multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…These factors contribute to higher awareness of a broader diversity of parasite species in humans than in other hosts. Although we applied ecological methods to control for study effort [ 11 ] and focused on country-level data, human parasite research—and thus, discovery—may be biased in unique ways that are not fully addressed through the use of these methods. For example, given interests in public health, research has devoted much effort to resolving viral lineages in humans, which could inflate measures of viral richness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors contribute to higher awareness of a broader diversity of parasite species in humans than in other hosts. Although we applied ecological methods to control for study effort [ 11 ] and focused on country-level data, human parasite research—and thus, discovery—may be biased in unique ways that are not fully addressed through the use of these methods. For example, given interests in public health, research has devoted much effort to resolving viral lineages in humans, which could inflate measures of viral richness.…”
Section: Discussionmentioning
confidence: 99%
“…The Chao2 method estimates species richness from patterns of incidence across sampling events [ 30 ]. Based on analysis of artificial datasets simulated to mimic the structure of the Global Mammal Parasite Database, we previously found that estimating richness using Chao2 is relatively more precise and unbiased than other methods of controlling for uneven sampling effort across species, and especially useful for making comparisons across species [ 11 ]. In this study, we thus use an estimate of species richness that is based on patterns of parasite species discovery in different studies, rather than an observed value (although we refer to this value as “observed” to draw a contrast with the predicted values, see below).…”
Section: Methodsmentioning
confidence: 99%
“…For example, terrestrial primate species are more likely to be sampled for parasites than arboreal primate species ( Cooper and Nunn, 2013 ; Poulin et al, 2016 ). Thus, a variety of approaches have been developed to deal with variation in sampling effort ( Nunn et al, 2003 ; Elmasri et al, 2020 ; Teitelbaum et al, 2020 ; Amoroso and Nunn, 2021 ).…”
Section: Investigating Distributions Of Parasite Sharing Among Hostsmentioning
confidence: 99%
“…This relationship could explain the common observation that fast-lived host species (i.e., those that favour reproduction over survival) tend to disproportionately source zoonotic parasites (Keesing et al 2010;Ostfeld et al 2014;. Complicating matters, a given species' observed parasite diversity depends inherently on the effort that has been directed towards examining it (Olival et al 2017;Gutiérrez et al 2019;Teitelbaum et al 2019;Mollentze & Streicker 2020). Such research effort is heterogeneously distributed in space (Allen et al 2017;Olival et al 2017;Jorge & Poulin 2018) and across mammal species, particularly with regards to life history and taxonomy (Olival et al 2017;Mollentze & Streicker 2020).…”
Section: Introductionmentioning
confidence: 99%